Plain Water and Sugar-Sweetened Beverage Consumption in Relation to Energy and Nutrient Intake at Full-Service Restaurants - An, Ruopeng (Nutrients, 2016)
Background: Drinking plain water, such as tap or bottled water, provides hydration and satiety without adding calories. We examined plain water and sugar-sweetened beverage (SSB) consumption in relation to energy and nutrient intake at full-service restaurants. Methods: Data came from the 2005–2012 National Health and Nutrition Examination Survey, comprising a nationally-representative sample of 2900 adults who reported full-service restaurant consumption in 24-h dietary recalls. Linear regressions were performed to examine the differences in daily energy and nutrient intake at full-service restaurants by plain water and SSB consumption status, adjusting for individual characteristics and sampling design. Results: Over 18% of U.S. adults had full-service restaurant consumption on any given day. Among full-service restaurant consumers, 16.7% consumed SSBs, 2.6% consumed plain water but no SSBs, and the remaining 80.7% consumed neither beverage at the restaurant. Compared to onsite SSB consumption, plain water but no SSB consumption was associated with reduced daily total energy intake at full-service restaurants by 443.4 kcal, added sugar intake by 58.2 g, saturated fat intake by 4.4 g, and sodium intake by 616.8 mg, respectively. Conclusion: Replacing SSBs with plain water consumption could be an effective strategy to balance energy/nutrient intake and prevent overconsumption at full-service restaurant setting.